From a Hobby to a Business: Drifting through Paradox While the Business Accelerates - Cunha, Miguel Pina e; Clegg, Stewart; Rego, Arménio; Giustiniano, Luca (Organizações & Sociedade, 2024)
Our longitudinal case study investigates the emergence of an embryonic business from a hobby. As the hobby evolved to become an entrepreneurial venture, the dimensions of play and work engaged in a paradoxical tension that dynamically persisted, spiraling, as the business unfolded. The process of turning a hobby into a business progressively imbricated two opposing disciplines, those of play and work. As a result, inherent tensions between them have to be managed. Turning these tensions into a source of vitality to be nurtured, rather than framing the tension as a dichotomy to be solved, is seen to be vital to the continuation of the venture.